CLINICAL EFFICACY OF PHALTRIKADI KWATH IN CONTROLLING BLOOD SUGAR LEVEL IN PRAMEHA (TYPE 2 DIABETES MELLITUS - Gouri, Chauhan; Arun Kumar, *Mahapatra; Kapoor Alka, Babar; Abhimanyu, Kumar (AYUSHDHARA, 2015)
Prameha is also known as diabetes mellitus (DM) in which there is excess and frequent passage of abnormal urine. Also DM is a group of metabolic disease, in which there is high blood sugar levels over a prolonged period, producing symptoms of excess thirst, hunger and urine. It can be kept under control with appropriate diet, exercise and if required medicine. Phalatrikadi kwath is a well known drug used in the treatment of all kinds of diabetes. Aim: the present study was conducted to evaluate the efficacy of Phalatrikadi kwath in controlling blood sugar level. Methods and Material: 35 patients with high blood sugar (fasting >110 mg/dl, postprandial sugar >140 mg/dl) level of either sex attending the OPD of all India Institute of Ayurveda were selected and Phalatrikadi kwath in the dose of 40 ml was given at bed time for eight weeks with modification in diet and lifestyle instruction. Blood sugar level was tested every fifteen days. The result was analyzed by applying paired t test to the data using SPSS software. Result: It was found that the mean value of fasting and PP sugar level before treatment was 193.20 + 78.782 and 275.96 + 95.678 respectively and that after 8 weeks of treatment was 112.76 and 144.52 respectively. The treatment gave a difference of 80.44 in fasting and 131.44 mg/dl sugar level in postprandial state which is found to be highly statistical significant (P value <0.001). Conclusion: Phalatrikadi kwath is a safe and efficacious treatment for all type of Prameha (type II DM) cases whether old or new.